The adoption of Building Information Modelling (BIM) uses in the construction phase for BIM based projects: the contractors’ perspective / Wan Nur Syazwani Wan Mohammad, Mohd Rofdzi Abdullah and Sallehan Ismail - Wan Mohammad, Wan Nur Syazwani; Abdullah, Mohd Rofdzi; Ismail, Sallehan (2021)
Of-late, the trend of digitalization, automation and the use of Information and Communications Technology (ICT) in the Construction industry which encompasses Internet of Things (IoT) and cloud computing are defined as the Fourth Industrial Revolution 4.0 (IR 4.0). Thus, as IR4.0 introduces digital technology, Building Information Modelling (BIM) has become the main accelerator in producing digital information for construction projects. Through BIM, the construction information is stored, supplied and received in one single respiratory system which enables the BIM-based project team to interact and collaborate in real-time throughout the project life cycle. Nevertheless, the adoption of BIM in the Malaysian Construction Industry and particularly for contractors are relatively low. This is because contractors have no profound understanding of BIM and its requirements. Hence, this study aims to determine the significant uses of BIM from the contractor’s perspective which covers six (6) uses during the construction phase. To do so, a cross-sectional survey was conducted inside the Malaysian Construction Industry particularly for BIM-based project contractors. As a result, the 3D coordination and the record model remarked the top significant uses in the construction phase. This shows that the uses of BIM are to minimize the discrepancy of drawings and visualizations and to create a record model for facility management purposes. Thus, the results of the study also provide insight to the project teams especially contractors, clients, consultants and other stakeholders take into consideration the uses of BIM for future BIM-based projects.